Variables emocionales asociadas a intentos de suicidio en adolescentes atendidos en el Hospital Regional de Loreto, Iquitos 2017-2018 - Paz Cabezas, Carlos Juan (2024)
The objective of the study was to determine the relationship between the emotional variables of Anxiety, Depression and suicide attempts in adolescents treated at the Loreto Regional Hospital in the city of Iquitos in the years 2017-2018. The research method was quantitative, descriptive, retrospective, non-experimental in design, in a total population of 748 adolescents served, of which the sample was 39 adolescents with a diagnosis of attempted suicide. The instrument was a registration form in which sociodemographic data, data on emotional variables and suicide attempts in adolescents were recorded. The main findings were: 53.85% had severe anxiety, 25.64% had moderate anxiety, 15.35% had mild anxiety, and 5.12% had no anxiety. 35.89% presented mild depression, 30.76% moderate depression, 23.07% severe depression and 10.25% without depression. 38.46% attempted suicide by self-harm, 33.33% by drug poisoning and 28.20% by organ phosphorus poisoning; determining that there is a significant statistical association between the emotional variable severe anxiety and suicide attempts due to self-harm (p=0.001) and there was no statistical significance between the variable mild depression and suicide attempts due to self-harm (p=0.227). The conclusion is that adolescents who attempted suicide showed a predominance of severe anxiety and mild depression.